An Analysis of Student Learning Style in Learning English in Sekolah Indonesia Kuala Lumpur, Malaysia - Muhammad Rafiq; Asep Hardiyanto; Sumarno Sumarno (Universitas Hamzanwadi, 2023)
Learning style is one way to find out a person's most comfortable way in the learning process being carried out. In the learning process takes place, students have their learning style preferences. Learning styles have four preference models, namely VARK; visual, aural, read/write, and kinesthetic. The VARK can help students' learning style preferences in maximizing their learning style. Thus, the gap in this research is the investigation of learning styles in the English as a Second Language (ESL) context. The purposes of this study were to find out; (1) the learning styles employed by students and (2) the dominant learning style employed by the students in Sekolah Indonesia Kuala Lumpur, Malaysia in learning English. This research used a descriptive quantitative research method that deals with the types of learning styles by VARK Neil Fleming. The total participants of the research were 28 students. The findings showed that (1) it was found that in the ESL context, students prefer to use two learning style preferences, namely; unimodal and bimodal, and (2) students predominantly used the kinesthetic learning style. The current findings implied that ESL teachers should provide English learning activities which is able to trigger students to engage directly in the process of teaching and learning in the classroom so that they can use their learning style maximally. Furthermore, the teaching process should emphasize on students—centered learning in order that students will be easier in reaching the objectives of Learning English in ESL context.